2015
DOI: 10.1007/s10753-015-0233-y
|View full text |Cite|
|
Sign up to set email alerts
|

Fisetin Alleviates Lipopolysaccharide-Induced Acute Lung Injury via TLR4-Mediated NF-κB Signaling Pathway in Rats

Abstract: Conclusion: In human infection with H7N9 virus, ALI/ARDS was an important cause of its fatal prognosis. The low expression of cIAP2 inhibited its combination with RIPK1, which caused the combination of RIPK1 and RIPK3.Necroptosis was then induced with the recruitment and activation of MLKL, which destructed the airway epithelium cells followed with ALI/ARDS and triggered the deaths of patients. Background and Objective: We investigated the effect of induced pluripotent stem cells (iPSCs) in moderating pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
(34 reference statements)
2
27
0
Order By: Relevance
“…In addition, the CS-induced inflammatory cell population in BALF was markedly reduced in fisetin-treated rats supporting the preventive effects of fisetin against CS-induced lung tissue damage. Supporting our findings, fisetin has been shown to rescue different organs from inflammation-induced tissue damage (Feng, Jiang, Sun, Fu, & Li, 2016;Prasath, Sundaram, & Subramanian, 2013;Sahu et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the CS-induced inflammatory cell population in BALF was markedly reduced in fisetin-treated rats supporting the preventive effects of fisetin against CS-induced lung tissue damage. Supporting our findings, fisetin has been shown to rescue different organs from inflammation-induced tissue damage (Feng, Jiang, Sun, Fu, & Li, 2016;Prasath, Sundaram, & Subramanian, 2013;Sahu et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…[32,33] In the LPSstimulated ALI model, it is well-known that toll-like receptor-4 (TLR4)-mediated Nf-kβ activation increases the expression of TNF-α and IL-6 proinflammatory cytokines, and both these cytokines activate Nf-kβ. [31,34] In our study, administration of hesperetin was shown to reduce Nf-kβ immunoreactivity in the LPS+hesperetin group, leading to a significant reduction in TNF-α, IL-6, and IL-1β expression, compared to the LPS group. Also, hesperetin caused a non-significant increase in the anti-inflammatory IL-10 level compared to the LPS group (p= 0.15).…”
Section: Discussionsupporting
confidence: 50%
“…[29,30] The Nf-kβ is an important transcription factor which plays a central role in the regulation of immune responses, including the expression of genes of many inflammatory cytokines. [31] Previous studies have demonstrated that Nf-kβ regulates the inflammatory and immune response to extracellular stimuli and plays a pivotal role in ALI development. [32,33] In the LPSstimulated ALI model, it is well-known that toll-like receptor-4 (TLR4)-mediated Nf-kβ activation increases the expression of TNF-α and IL-6 proinflammatory cytokines, and both these cytokines activate Nf-kβ.…”
Section: Discussionmentioning
confidence: 99%
“…Also, fisetin was found to activate Nrf2 mediated induction of hemeoxygenase-1 (HO-1) important for cell survival under oxidative stress conditions [23]. More recent studies have found that fisetin attenuates oxidant-driven activation of c-Jun N-terminal protein kinase (JNK) and nuclear factor-kappa B (NF-κB) signaling pathways [24,25]. These data suggest a possible use of fisetin as a potent anti-oxidant in a wide variety of biological conditions.…”
Section: Anti-oxidant Activity Of Fisetinmentioning
confidence: 99%